A produção memorialística de Hilda Siri publicada no almanaque Serra Post Kalender - Pretzel, Sílvia (2010)
This paper presents a description of the history of German immigration to the central region of Rio Grande do Sul. This is the initial study that has the sequence showing the development of German-language printed and its attempt to preserve the history of this nation. To illustrate this attempt to preserve, it are analyzed in this work, the five stories of Hilda Siri, published in the almanac Serra Post Kalender between the years 1952 and 1956. This almanac was chosen because it marks the time when circulated (1922 1960) and the author presents relevant texts in the years when she published in this almanac, focusing in large part on remembering. This work is divided into four chapters, respectively, the history of immigration, of the theories on memory and history, the press in German journalism in Southern Brazil and literary analysis of the stories by Hilda Siri. In this analysis the points are seen as historic and that are relevant to the development of these texts.